Environment-friendly packaging material and preparation method thereof

By adopting a double-layer structure environmentally friendly packaging material, combined with low-density polyethylene, modified montmorillonite and sagittal extract, the shortcomings of existing polyethylene packaging materials in terms of mechanical, antibacterial and barrier properties are solved, and better food protection and shelf life are achieved.

CN119659124AActive Publication Date: 2025-03-21LOGOS PACKAGING HUIZHOU CO LTD

Patent Information

Application Number
CN202411872214.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-21
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The existing film packaging materials with polyethylene as substrates have shortcomings in terms of mechanical properties, antibacterial properties and ability to block oxygen and water, and cannot effectively protect food and extend its shelf life.

Method used

An environmentally friendly packaging material with a double-layer structure, the inner layer contains low-density polyethylene, metallocene linear low-density polyethylene, ethylene-vinyl alcohol copolymer and nano zinc oxide, and the surface layer contains modified montmorillonite and sagitta extract, which is prepared by hot pressing composite technology.

Benefits of technology

The excellent mechanical properties, good antibacterial properties and improved barrier properties of the material are achieved, which can more effectively protect food and extend its shelf life.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of packaging materials, and particularly relates to an environment-friendly packaging material and a preparation method thereof. The packaging material comprises an inner layer and a surface layer which are sequentially arranged, the inner layer is prepared from the following raw materials in parts by weight: 65 to 85 parts of low-density polyethylene, 20 to 30 parts of metallocene linear low-density polyethylene, 5 to 10 parts of ethylene-vinyl alcohol copolymer and 1 to 2 parts of nano zinc oxide; the surface layer is prepared from the following raw materials in parts by weight: 20 to 25 parts of low-density polyethylene, 60 to 70 parts of medium-density polyethylene, 8 to 12 parts of modified montmorillonite and 1 to 5 parts of sedum sarmentosum extract. The environment-friendly packaging material has better barrier property and antibacterial property, and also has excellent mechanical property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of packaging materials, and in particular relates to an environmentally friendly packaging material and a preparation method thereof. Background Art

[0002] With the continuous advancement of science and technology, polymer materials such as plastic packaging have gradually been used in people's daily lives, bringing great convenience to life. Among various plastic packaging materials, polyethylene is made into plastic bags, cling film, food bags and other items because it is odorless, tasteless, non-toxic, has high transparency and excellent processing properties. It can be seen that polyethylene has broad application prospects in the field of packaging materials.

[0003] However, it is found in practical applications that the mechanical properties of the film packaging material obtained with polyethylene as the substrate are poor, and it cannot meet the impact and other external forces that the items are subjected to during transportation, which ultimately greatly reduces the packaging effect. Especially when used for food packaging, the rupture of the packaging material will cause the food to be exposed to the air for a long time, causing the food to spoil quickly and fail to achieve the purpose of preserving food. At the same time, since polyethylene does not have antibacterial properties, the film packaging material with polyethylene as the substrate does not have antibacterial properties. In addition, the film packaging material obtained with polyethylene as the substrate also has the problem of insufficient ability to block oxygen and water and easy oxidation. Based on the above background, it is urgent to conduct an in-depth exploration of the performance of film packaging materials with polyethylene as the substrate, so as to accelerate the application of polyethylene in the field of packaging materials. Summary of the invention

[0004] The first object of the present invention is to provide an environmentally friendly packaging material, which has good barrier properties, antibacterial properties, and excellent mechanical properties.

[0005] The second object of the present invention is to provide a method for preparing an environmentally friendly packaging material, which is simple and easy to operate.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] An environmentally friendly packaging material, comprising an inner layer and a surface layer which are arranged in sequence; the inner layer comprises the following raw materials in parts by weight: 65-85 parts of low-density polyethylene, 20-30 parts of metallocene linear low-density polyethylene, 5-10 parts of ethylene-vinyl alcohol copolymer, and 1-2 parts of nano zinc oxide; the surface layer comprises the following raw materials in parts by weight: 20-25 parts of low-density polyethylene, 60-70 parts of medium-density polyethylene, 8-12 parts of modified montmorillonite, and 1-5 parts of creeping celestial being extract.

[0008] Furthermore, the preparation process of the modified montmorillonite is as follows:

[0009] (1) adding the pretreated montmorillonite into an ethanol aqueous solution, then adding vinyltriethoxysilane to carry out heating and stirring reaction, and obtaining the first modified montmorillonite after purification;

[0010] (2) adding the first modified montmorillonite in step (1) into DMF, and then adding polyethylene glycol methacrylate and azobisisobutyronitrile to carry out heating reaction to obtain modified montmorillonite.

[0011] Furthermore, in step (2), the mass ratio of the first modified montmorillonite, polyethylene glycol methacrylate, and azobisisobutyronitrile is 1:(0.1-0.2):(0.008-0.012); the temperature of the heating reaction is 80-90° C., and the heating reaction time is 4-5 hours.

[0012] Furthermore, in step (1), the mass ratio of the pretreated montmorillonite to vinyltriethoxysilane is 1:(0.1-0.2); the temperature of the heating and stirring reaction is 55-65°C, and the time of the heating and stirring reaction is 3-4h; and the volume ratio of ethanol to water in the ethanol-water solution is 1:(0.2-0.4).

[0013] Furthermore, the preparation method of the pretreated montmorillonite is as follows:

[0014] According to the mass ratio of montmorillonite, sodium hydroxide solution and manganese chloride solution being 1:(8-11):(1-3), montmorillonite is added to a sodium hydroxide solution with a mass fraction of 6-9% for heating reaction, and then a manganese chloride solution with a mass fraction of 8-12% is added for stirring, and then filtered, washed, dried and calcined to obtain the product.

[0015] Furthermore, the heating reaction temperature is 65-75°C, and the heating reaction time is 1.5-2.5h; the stirring time is 1.5-2.5h; the calcination temperature is 300-400°C, and the calcination time is 4-5h.

[0016] Furthermore, the melt index of the low-density polyethylene is 1.0-2.0 g / 10 min; the melt index of the metallocene linear low-density polyethylene is 3.0-4.0 g / 10 min; the melt index of the medium-density polyethylene is 0.18-0.22 g / 10 min; the molar content of ethylene in the ethylene-vinyl alcohol copolymer is 25-35%; the weight average molecular weight of the ethylene-vinyl alcohol copolymer is (16-36)×10 4 g / moL.

[0017] Furthermore, the thickness of the surface layer is 10-12 μm, and the thickness of the inner layer is 20-30 μm.

[0018] The method for preparing the above-mentioned environmentally friendly packaging material comprises the following steps:

[0019] a. Preparation of the surface layer: According to the weight ratio, the raw materials for the surface layer are uniformly mixed and the surface layer is formed by melt blending;

[0020] b. Preparation of the inner layer: According to the weight ratio, the raw materials for the inner layer are uniformly mixed and the inner layer is formed by melt blending;

[0021] c. Preparation of environmentally friendly packaging materials: The surface layer prepared in step a and the inner layer prepared in step b are stacked in sequence and then hot-pressed to prepare environmentally friendly packaging materials.

[0022] Furthermore, the temperature of the melt blending in step a and step b is 160-170°C.

[0023] Compared with the prior art, the beneficial effects of the present invention are mainly:

[0024] 1. The environmentally friendly packaging material provided by the present invention includes a surface layer and an inner layer, and modified montmorillonite, scutellaria baicalensis extract and other ingredients are added to the surface layer. The modified montmorillonite has good dispersibility and compatibility in the matrix material, and can form a network structure with the polyethylene matrix, thereby improving the density of the material, and further improving its barrier properties to water vapor and oxygen. The scutellaria baicalensis extract can be adsorbed by the modified montmorillonite, which improves its dispersibility and stability in the packaging material, thereby better exerting an antibacterial effect. Furthermore, the present invention also adds an antibacterial ingredient, nano zinc oxide, to the inner layer, and the scutellaria baicalensis extract and nano zinc oxide jointly improve the antibacterial properties of the material.

[0025] 2. The environmentally friendly packaging material of the present invention has good barrier properties and antibacterial properties, as well as excellent mechanical properties. DETAILED DESCRIPTION

[0026] The technical scheme of the present invention is further described below in conjunction with specific embodiments. However, it should be understood by those skilled in the art that the following examples are only used to illustrate the present invention and should not be regarded as limiting the present invention. The specific conditions not specified in the examples are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, unless otherwise specified, are conventional products obtained through commercial channels.

[0027] The low-density polyethylene used in the embodiment of the present invention is BASF 24200H, with a melt index of 1.0-2.0 g / 10 min; the metallocene linear low-density polyethylene is ExxonMobil 3518PA, with a melt index of 3.0-4.0 g / 10 min; the medium-density polyethylene is Borealis MDPE FB2230, with a melt index of 0.18-0.22 g / 10 min.

[0028] 1. Embodiment

[0029] Example 1

[0030] Embodiment 1 provides an environmentally friendly packaging material, which comprises an inner layer and a surface layer arranged in sequence; the inner layer comprises the following raw materials in parts by weight: 72 parts of low-density polyethylene, 26 parts of metallocene linear low-density polyethylene, 8 parts of ethylene-vinyl alcohol copolymer, and 1.5 parts of nano zinc oxide; the surface layer comprises the following raw materials in parts by weight: 22 parts of low-density polyethylene, 64 parts of medium-density polyethylene, 9 parts of modified montmorillonite, and 4 parts of creeping lily extract; wherein the molar content of ethylene in the ethylene-vinyl alcohol copolymer is 30%, and the weight average molecular weight of the ethylene-vinyl alcohol copolymer is 33×10 4 g / moL.

[0031] The preparation process of the modified montmorillonite is as follows:

[0032] (1) According to the mass ratio of montmorillonite, sodium hydroxide solution and manganese chloride solution of 1:10:2, montmorillonite was added to a sodium hydroxide solution with a mass fraction of 8%, heated at 70°C for 2 hours, and then a manganese chloride solution with a mass fraction of 9% was added and stirred for 2 hours; after filtering, washing and drying, calcining at 350°C for 4.5 hours to obtain pretreated montmorillonite; according to the mass ratio of pretreated montmorillonite and vinyl triethoxysilane of 1:0.15, the pretreated montmorillonite was added to an ethanol aqueous solution (the volume ratio of ethanol to water was 1:0.3), and then vinyl triethoxysilane was added, heated and stirred at 60°C for 3.5 hours, filtered, washed and dried to obtain the first modified montmorillonite;

[0033] (2) According to the mass ratio of the first modified montmorillonite, polyethylene glycol methacrylate and azobisisobutyronitrile of 1:0.15:0.01, the first modified montmorillonite of step (1) is added to DMF, and then polyethylene glycol methacrylate and azobisisobutyronitrile are added, and the mixture is heated at 85° C. for 4.5 hours. After the reaction is completed, the mixture is filtered, washed and dried to obtain the modified montmorillonite.

[0034] Example 1 also provides a method for preparing the above-mentioned environmentally friendly packaging material, and the specific process is as follows:

[0035] a. Preparation of the surface layer: According to the weight ratio, the raw materials of the surface layer are uniformly mixed, melt-blended at 165°C, and then extruded through an extruder at 165°C, a screw speed of 20rpm, and a pulling speed of 15m / min. The sheet layer is then stretched at 145°C and the pulling speed is adjusted to be heat-treated at 90°C, and finally cooled at 30°C and a wind speed of 1.2m / s to form a surface layer with a thickness of 10μm;

[0036] b. Preparation of the inner layer: According to the weight ratio, the raw materials of the inner layer were uniformly mixed, melt blended at 165 ° C, and then extruded by an extruder at 165 ° C, a screw speed of 20 rpm, and a pulling speed of 15 m / min. The sheet was then stretched at 145 ° C and the pulling speed was adjusted to be heat-treated at 90 ° C, and finally cooled at 30 ° C and a wind speed of 1.2 m / s to form an inner layer with a thickness of 28 μm;

[0037] c. Preparation of environmentally friendly packaging materials: The surface layer prepared in step a and the inner layer prepared in step b are stacked in sequence, and then hot-pressed and laminated at 180° C. and 20 bar to prepare environmentally friendly packaging materials.

[0038] Example 2

[0039] Embodiment 2 provides an environmentally friendly packaging material, which includes an inner layer and a surface layer arranged in sequence; the inner layer includes the following raw materials in parts by weight: 65 parts of low-density polyethylene, 20 parts of metallocene linear low-density polyethylene, 5 parts of ethylene-vinyl alcohol copolymer, and 1 part of nano zinc oxide; the surface layer includes the following raw materials in parts by weight: 20 parts of low-density polyethylene, 60 parts of medium-density polyethylene, 8 parts of modified montmorillonite, and 1 part of creeping lily extract; wherein the molar content of ethylene in the ethylene-vinyl alcohol copolymer is 25%, and the weight average molecular weight of the ethylene-vinyl alcohol copolymer is 16×10 4 g / moL.

[0040] The preparation process of the modified montmorillonite is as follows:

[0041] (1) According to the mass ratio of montmorillonite, sodium hydroxide solution and manganese chloride solution of 1:8:1, montmorillonite is added to a sodium hydroxide solution with a mass fraction of 6%, and heated at 65°C for reaction for 2.5 hours. After the reaction is completed, an 8% manganese chloride solution is added and stirred for 2.5 hours; after filtering, washing and drying, calcining at 300°C for 5 hours to obtain pretreated montmorillonite; according to the mass ratio of pretreated montmorillonite and vinyl triethoxysilane of 1:0.1, the pretreated montmorillonite is added to an ethanol aqueous solution (the volume ratio of ethanol to water is 1:0.2), and then vinyl triethoxysilane is added, and heated and stirred at 55°C for reaction for 4 hours. After filtering, washing and drying, the first modified montmorillonite is obtained;

[0042] (2) adding the first modified montmorillonite of step (1) into DMF, and then adding polyethylene glycol methacrylate and azobisisobutyronitrile, according to the mass ratio of the first modified montmorillonite, polyethylene glycol methacrylate and azobisisobutyronitrile of 1:0.1:0.008, heating at 80° C. for reaction for 5 h, filtering, washing and drying after the reaction is completed to obtain modified montmorillonite.

[0043] Example 2 also provides a method for preparing the above-mentioned environmentally friendly packaging material, and the specific process is as follows:

[0044] a. Preparation of the surface layer: According to the weight ratio, the raw materials of the surface layer are uniformly mixed, melt-blended at 160°C, and then extruded through an extruder at 160°C, a screw speed of 20rpm, and a pulling speed of 15m / min. The sheet layer is then stretched at 145°C and the pulling speed is adjusted to be heat-treated at 90°C, and finally cooled at 30°C and a wind speed of 1.2m / s to form a surface layer with a thickness of 11μm;

[0045] b. Preparation of the inner layer: According to the weight ratio, the raw materials for the inner layer were uniformly mixed, melt blended at 160 ° C, and then extruded by an extruder at 160 ° C, a screw speed of 20 rpm, and a pulling speed of 15 m / min. The sheet was then stretched at 145 ° C and the pulling speed was adjusted to be heat-treated at 90 ° C, and finally cooled at 30 ° C and a wind speed of 1.2 m / s to form an inner layer with a thickness of 20 μm;

[0046] c. Preparation of environmentally friendly packaging materials: The surface layer prepared in step a and the inner layer prepared in step b are stacked in sequence, and then hot-pressed and laminated at 180° C. and 20 bar to obtain environmentally friendly packaging materials.

[0047] Example 3

[0048] Embodiment 3 provides an environmentally friendly packaging material, which comprises an inner layer and a surface layer arranged in sequence; the inner layer comprises the following raw materials in parts by weight: 85 parts of low-density polyethylene, 30 parts of metallocene linear low-density polyethylene, 10 parts of ethylene-vinyl alcohol copolymer, and 2 parts of nano zinc oxide; the surface layer comprises the following raw materials in parts by weight: 25 parts of low-density polyethylene, 70 parts of medium-density polyethylene, 12 parts of modified montmorillonite, and 5 parts of creeping lily extract; wherein the molar content of ethylene in the ethylene-vinyl alcohol copolymer is 35%, and the weight average molecular weight of the ethylene-vinyl alcohol copolymer is 36×10 4 g / moL.

[0049] The preparation process of the modified montmorillonite is as follows:

[0050] (1) According to the mass ratio of montmorillonite, sodium hydroxide solution and manganese chloride solution of 1:11:3, montmorillonite is added to a sodium hydroxide solution with a mass fraction of 9%, and heated at 75°C for reaction for 1.5 hours. After the reaction is completed, a manganese chloride solution with a mass fraction of 12% is added and stirred for 1.5 hours; after filtering, washing and drying, calcining at 400°C for 4 hours to obtain pretreated montmorillonite; according to the mass ratio of pretreated montmorillonite and vinyl triethoxysilane of 1:0.2, the pretreated montmorillonite is added to an ethanol aqueous solution (the volume ratio of ethanol to water is 1:0.4), and then vinyl triethoxysilane is added, and heated and stirred at 65°C for reaction for 3 hours, and filtered, washed and dried to obtain the first modified montmorillonite;

[0051] (2) adding the first modified montmorillonite of step (1) into DMF, and then adding polyethylene glycol methacrylate and azobisisobutyronitrile, according to the mass ratio of the first modified montmorillonite, polyethylene glycol methacrylate and azobisisobutyronitrile of 1:0.2:0.012, heating at 90° C. for 4 h, filtering, washing and drying after the reaction is completed, and obtaining modified montmorillonite.

[0052] Example 3 also provides a method for preparing the above-mentioned environmentally friendly packaging material, and the specific process is as follows:

[0053] a. Preparation of the surface layer: According to the weight ratio, the raw materials of the surface layer are uniformly mixed, melt-blended at 170°C, and then extruded through an extruder at 170°C, a screw speed of 20rpm, and a pulling speed of 15m / min. The sheet layer is then stretched at 145°C and the pulling speed is adjusted to be heat-treated at 90°C, and finally cooled at 30°C and a wind speed of 1.2m / s to form a surface layer with a thickness of 12μm;

[0054] b. Preparation of the inner layer: According to the weight ratio, the raw materials for the inner layer were uniformly mixed, melt blended at 170 ° C, and then extruded through an extruder at 170 ° C, a screw speed of 20 rpm, and a pulling speed of 15 m / min. The sheet was then stretched at 145 ° C and the pulling speed was adjusted to be heat-treated at 90 ° C, and finally cooled at 30 ° C and a wind speed of 1.2 m / s to form an inner layer with a thickness of 30 μm;

[0055] c. Preparation of environmentally friendly packaging materials: The surface layer prepared in step a and the inner layer prepared in step b are stacked in sequence, and then hot-pressed and laminated at 180° C. and 20 bar to prepare environmentally friendly packaging materials.

[0056] 2. Comparative Example

[0057] Comparative Example 1

[0058] The difference between Comparative Example 1 and Example 1 is that:

[0059] The surface layer comprises the following raw materials in parts by weight: 22 parts of low-density polyethylene, 64 parts of medium-density polyethylene, and 4 parts of Creeping Jasmine extract.

[0060] Comparative Example 2

[0061] The difference between Comparative Example 2 and Example 1 is that:

[0062] Montmorillonite and polyethylene glycol methacrylate are used to replace modified montmorillonite, wherein the mass ratio of montmorillonite to polyethylene glycol methacrylate is 1:0.15.

[0063] Comparative Example 3

[0064] The difference between Comparative Example 3 and Example 1 is that:

[0065] The first modified montmorillonite and polyethylene glycol methacrylate are used to replace the modified montmorillonite, wherein the mass ratio of the first modified montmorillonite to the polyethylene glycol methacrylate is 1:0.15.

[0066] Comparative Example 4

[0067] The difference between Comparative Example 4 and Example 1 is that:

[0068] The surface layer comprises the following raw materials in parts by weight: 22 parts of low-density polyethylene, 64 parts of medium-density polyethylene, and 9 parts of modified montmorillonite.

[0069] 3. Test examples

[0070] The properties of the packaging materials obtained in Examples 1-3 and Comparative Examples 1-4 were tested, and the specific testing methods are as follows:

[0071] (1) Antibacterial properties

[0072] The test was conducted according to QB / T 2591-2003 "Antibacterial Plastics - Test Methods for Antibacterial Performance and Antibacterial Effect" (film method). The tested bacteria were Escherichia coli and Staphylococcus aureus. Each group of samples was placed at room temperature for 10 days, then cleaned and dried before testing. The results are shown in Table 1.

[0073] (2) Barrier properties

[0074] Oxygen permeability: refer to the standard "GB / T 19789-2005 Packaging materials, plastic films and sheets oxygen permeability test" coulometric test method to test oxygen permeability. The results are shown in Table 2.

[0075] Water vapor permeability: The water vapor permeability of the film was tested with reference to the standard GB / T 21529-2008. The results are shown in Table 2.

[0076] (3) Mechanical properties

[0077] Tensile strength: refer to standard GB / T 1040.1-2018, the tensile speed is 50mm / min, the tensile force is 1000N, the results are shown in Table 3;

[0078] Elongation at break: refer to standard GB / T 1040.1-2018, the tensile speed is 50 mm / min, the tensile force is 1000 N, and the results are shown in Table 3.

[0079] Table 1

[0080] Packaging material / antibacterial rate (%) Escherichia coli Staphylococcus aureus Example 1 98.9 97.3 Example 2 98.6 97.1 Example 3 98.4 96.7 Comparative Example 1 97.2 95.2 Comparative Example 2 97.5 95.5 Comparative Example 3 97.9 96.1 Comparative Example 4 95.1 93.6

[0081] Table 2

[0082] Packaging materials / barrier properties <![CDATA[Oxygen transmission rate (cm 3 / m 2 / day / Pa)]]> <![CDATA[Water vapor transmission rate (g / m 2 / day)]]> Example 1 385 1.2 Example 2 390 1.3 Example 3 394 1.5 Comparative Example 1 497 6.3 Comparative Example 2 465 4.6 Comparative Example 3 448 3.7 Comparative Example 4 403 1.6

[0083] Table 3

[0084] Packaging materials / mechanical properties Tensile strength / MPa Elongation at break / % Example 1 40.1 633 Example 2 39.5 625 Example 3 39.2 617 Comparative Example 1 22.4 522 Comparative Example 2 27.8 551 Comparative Example 3 31.3 574 Comparative Example 4 39.0 610

[0085] It can be seen from Tables 1-3 that the packaging materials obtained in Examples 1-3 have good barrier properties and antibacterial properties, as well as excellent mechanical properties.

[0086] It can be seen from Table 1 that compared with Examples 1-3, the antibacterial performance of the packaging material is significantly reduced due to the omission of the Herba Lysimachiae extract in Comparative Example 4. Analysis shows that the Herba Lysimachiae extract can be adsorbed by the modified montmorillonite, which improves its dispersibility and stability in the packaging material, thereby better exerting the antibacterial effect.

[0087] As shown in Table 2, compared with Examples 1-3, Comparative Example 1 omits the modified montmorillonite component; Comparative Example 2 uses montmorillonite and polyethylene glycol methacrylate instead of modified montmorillonite; Comparative Example 3 uses the first modified montmorillonite and polyethylene glycol methacrylate instead of modified montmorillonite, all of which result in a significant decrease in the barrier properties of the packaging material. Analysis shows that after pretreatment, the internal pores of montmorillonite increase, which can extend the path for water and oxygen to pass through the packaging material. At the same time, the increase in specific surface area can also adsorb water and oxygen. The first modified montmorillonite, i.e., vinylized montmorillonite, can react with polyethylene glycol methacrylate, further improving the dispersibility and compatibility of montmorillonite in the matrix material, and the modified montmorillonite and the polyethylene matrix form a network structure, which improves the density of the material, thereby improving its barrier properties to water vapor and oxygen.

[0088] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. The basic principles and main features of the present invention have been described above with specific implementation schemes. On the basis of the present invention, some modifications or replacements may be made thereto, but these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of protection claimed by the present invention.

Claims

1. An environmentally friendly packaging material, characterized in that: The environmentally friendly packaging material includes an inner layer and a surface layer which are arranged in sequence; the inner layer includes the following raw materials in parts by weight: 65-85 parts of low-density polyethylene, 20-30 parts of metallocene linear low-density polyethylene, 5-10 parts of ethylene-vinyl alcohol copolymer, and 1-2 parts of nano zinc oxide; the surface layer includes the following raw materials in parts by weight: 20-25 parts of low-density polyethylene, 60-70 parts of medium-density polyethylene, 8-12 parts of modified montmorillonite, and 1-5 parts of creeping celestial being extract.

2. The environmentally friendly packaging material according to claim 1, characterized in that: The preparation process of the modified montmorillonite is as follows: (1) adding the pretreated montmorillonite into an ethanol aqueous solution, then adding vinyltriethoxysilane for heating and stirring to react, and obtaining the first modified montmorillonite after purification; (2) adding the first modified montmorillonite in step (1) into DMF, and then adding polyethylene glycol methacrylate and azobisisobutyronitrile to carry out heating reaction to obtain modified montmorillonite.

3. The environmentally friendly packaging material according to claim 2, characterized in that: In step (2), the mass ratio of the first modified montmorillonite, polyethylene glycol methacrylate and azobisisobutyronitrile is 1:(0.1-0.2):(0.008-0.012); the temperature of the heating reaction is 80-90° C., and the heating reaction time is 4-5 hours.

4. The environmentally friendly packaging material according to claim 2, characterized in that: The mass ratio of the pretreated montmorillonite to vinyl triethoxysilane in step (1) is 1:(0.1-0.2); the temperature of the heating and stirring reaction is 55-65°C, and the time of the heating and stirring reaction is 3-4h; the volume ratio of ethanol to water in the ethanol-water solution is 1:(0.2-0.4).

5. The environmentally friendly packaging material according to claim 4, characterized in that: The preparation method of the pretreated montmorillonite is as follows: According to the mass ratio of montmorillonite, sodium hydroxide solution and manganese chloride solution being 1:(8-11):(1-3), montmorillonite is added to a sodium hydroxide solution with a mass fraction of 6-9% for heating reaction, and then a manganese chloride solution with a mass fraction of 8-12% is added for stirring, and then filtered, washed, dried and calcined to obtain the product.

6. The environmentally friendly packaging material according to claim 5, characterized in that: The heating reaction temperature is 65-75°C, and the heating reaction time is 1.5-2.5h; the stirring time is 1.5-2.5h; the calcination temperature is 300-400°C, and the calcination time is 4-5h.

7. The environmentally friendly packaging material according to claim 1, characterized in that: The melt index of the low-density polyethylene is 1.0-2.0 g / 10 min; the melt index of the metallocene linear low-density polyethylene is 3.0-4.0 g / 10 min; the melt index of the medium-density polyethylene is 0.18-0.22 g / 10 min; the molar content of ethylene in the ethylene-vinyl alcohol copolymer is 25-35%; the weight average molecular weight of the ethylene-vinyl alcohol copolymer is (16-36)×10 4 g / moL.

8. The environmentally friendly packaging material according to claim 1, characterized in that: The thickness of the surface layer is 10-12 μm, and the thickness of the inner layer is 20-30 μm.

9. The method for preparing the environmentally friendly packaging material according to claim 1, characterized in that: The following steps are involved: a. Preparation of the surface layer: According to the weight ratio, the raw materials for the surface layer are uniformly mixed and the surface layer is formed by melt blending; b. Preparation of the inner layer: According to the weight ratio, the raw materials for the inner layer are uniformly mixed and the inner layer is formed by melt blending; c. Preparation of environmentally friendly packaging materials: The surface layer prepared in step a and the inner layer prepared in step b are stacked in sequence and then hot-pressed to prepare environmentally friendly packaging materials.

10. The method for preparing the environmentally friendly packaging material according to claim 9, characterized in that: The temperature of melt blending in step a and step b is 160-170°C.

Citation Information

Patent Citations

  • High-resistance antibacterial PE (polyethylene) film and preparation method thereof

    CN103205049A

  • Special polyvinyl alcohol thin film for fruit and vegetable packaging

    CN108794954A

  • Polyethylene type recyclable packaging material and preparation method thereof

    CN114889278A

  • Ultrahigh-glossiness ultralow-haze PE film and preparation method thereof

    CN117922132A

  • Antibacterial composition containing sedum sarmentosum extract

    KR1020120055481A

Cited By

  • Anti-aging antibacterial film and preparation method thereof

    CN120192610A

  • High-barrier PP / EVOH alloy material for blood sampling tube and preparation method of high-barrier PP / EVOH alloy material

    CN122234506A